Welfare effects of changed prices: The "tortilla crisis" revisited - Rita Motzigkeit Gonzalez (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2016)
This study uses a comprehensive framework to quantify the welfare changes of rural and non-rural households in Mexico associated with the food price crisis of 2007. The total change in welfare is decomposed into five contributors. I find that income effects, i.e. changes through profits and wages, negatively affected welfare. Substitution effects played an important role in maintaining welfare levels after a price shocks, households substantially substituted out of goods that showed a strong increase in their price. Though food price increases led to a significant welfare loss, part of it was compensated through the decrease of the price of other commodities such as health and personal care, transportation, and leisure. Hence, particularly in non-rural areas, the sole use of food commodities to analyze welfare changes leads to markedly different results than using the complete range of all goods consumed. Overall both poor households in rural as well as non-rural areas experienced a net welfare loss, but the effect was stronger for poor rural households thus among the poorest of the poor.
Keywords: D31; I31; I32; O15; 330; welfare changes; prices; poverty